2017
DOI: 10.1007/s12250-017-3987-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing a bacteriophage cocktail for biocontrol of potato bacterial wilt

Abstract: Bacterial wilt is a devastating disease of potato and can cause an 80% production loss. To control wilt using bacteriophage therapy, we isolated and characterized twelve lytic bacteriophages from different water sources in Kenya and China. Based on the lytic curves of the phages with the pathogen Ralstonia solanacearum, one optimal bacteriophage cocktail, P1, containing six phage isolations was formulated and used for studying wilt prevention and treatment efficiency in potato plants growing in pots. The preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…The phages P-PSG-11 and Wc4 used in this study have previously been shown to be potential biocontrol agents of the potato phytobacteria R. solanacearum [31] and P. carotovorum subsp. carotovorum [32], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phages P-PSG-11 and Wc4 used in this study have previously been shown to be potential biocontrol agents of the potato phytobacteria R. solanacearum [31] and P. carotovorum subsp. carotovorum [32], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…carotovorum (Pcc) and Pectobacterium atrosepticum (Pba) cause blackleg in the growing plant and soft rot in the potato tuber during storage and transportation [30]. Phages have been considered in the biocontrol of these phytopathogens [31,32]. A major challenge in phage-mediated biocontrol of phytopathogens is phage inactivation by UV light, desiccation, and excess heat.…”
Section: Of 14mentioning
confidence: 99%
“…Another method of preparing a phage cocktail would be selecting phages from an assemblage of phages based on phage lytic or lysis curves . A phage lytic curve is a measure of the bactericidal activity of lytic phages.…”
Section: Methods For the Development Of Phage Cocktailsmentioning
confidence: 99%
“…In field‐grown plants, phage cocktail application caused a decline in disease severity of ∼ 17%. Several other studies have demonstrated the feasibility of applying phage cocktails as biocontrol agents of phytopathogens . At the same time, they also showed that it is extremely important to have a good phage cocktail and the control efficacy of phage cocktails could be affected greatly by various factors.…”
Section: Previous Use Of Phage Cocktails As Biocontrol Agents Of Phytmentioning
confidence: 99%
“…It is worth mentioning that treatment with phage Wc5r proved effective against phage-resistant strains of P. carotovorum [77]; while phage ΦAS1 is an efficient therapy for potato common scab, produced by S. scabies, when used to treat seed tubers [70]. The study by Wei and colleagues, using a phage cocktail to combat the potato bacterial wilt caused by R. solanacearum, resulted in 80% of the plants protected against the bacterial pathogen [74].…”
Section: Potato Diseasesmentioning
confidence: 99%